Evaluation of Referral Ratios in Facing Universal Health Coverage in Primary Healthcare Centers (International Journal of Nursing Information, 2022)
Following the road map from the Social Security Agency for Health in the 2020-2025 period, a preventive approach is used for achieving universal health coverage. However, there are still disparities in the referral rate as an indicator of preventive efforts between cities and rural areas. The study aims to describe service referrals' achievements, the met capacity of human health resources, and the active participation of integrated health service posts for non-communicable diseases. The method used a quantitative approach. Research place in Cirebon City and Cirebon District, Indonesia. Referral rate data was collected in August-December 2019. The data on service capacities, health resources, and integrated health service participation was collected in August-December 2020. The result shows that the average referral rate in primary healthcare centers of Cirebon City was better than that of Cirebon District. The standard services in primary healthcare centers of Cirebon City were better than those in Cirebon District. The standard human resources in primary healthcare centers of Cirebon District were more qualified than those in Cirebon City. The active participation of integrated health service posts for non-communicable diseases in Cirebon City was better than in Cirebon District. The contribution of this article is to provide health care information about the evaluation of referral ratios in facing universal health coverage.